The careful selection of zwitterionic nanoparticle coating results in rapid and efficient cell labeling for imaging‐based cell tracking - Nicholas D. Calvert; Luciana Yu; Olivia C. Sehl; Julia J. Gevaert; Natasha N. Knier; Angelie Rivera‐Rodriguez; Clara S. Goulet; Nitara Fernando; Samantha Flood; Carlos M. Rinaldi‐Ramos; Paula J. Foster; Adam J. Shuhendler (Aggregate)
Abstract The increased clinical application of cell‐based therapies has resulted in a parallel increase in the need for non‐invasive imaging‐based approaches for cell tracking, often through labeling with nanoparticles. An ideal nanoparticle for such applications must be biologically compatible as well as readily internalized by cells to ensure adequate and stable cell loading. Surface coatings have been used to make nanoparticle trackers suitable for these purposes, but those currently employed tend to have cytotoxic effects. Zwitterionic ligands are known to be biocompatible and antifouling; however, head‐to‐head evaluation of specific zwitterionic ligands for cell loading has not yet been explored. Magnetic particle imaging (MPI) detects superparamagnetic iron oxide nanoparticles (SPIONs) using time‐varying magnetic fields. Because MPI can produce high‐contrast, real‐time images with no tissue depth limitation, it is an ideal candidate for in vivo cell tracking. In this work, we have conjugated hard (permanently charged) and soft (pKa‐dependently charged) biomimetic zwitterionic ligands to SPIONs and characterized how these ligands changed SPION physicochemical properties. We have evaluated cellular uptake and subcellular localization between zwitterions, how the improvement in cell uptake generated stronger MPI signal for smaller numbers of cells, and how these cells can be tracked in an animal model with greater sensitivity for longer periods of time. Our best‐performing surface coating afforded high cell loading within 4 h, with full signal retention in vivo over 7 days.